2010
DOI: 10.5194/acp-10-9931-2010
|View full text |Cite
|
Sign up to set email alerts
|

Bromide and other ions in the snow, firn air, and atmospheric boundary layer at Summit during GSHOX

Abstract: Abstract. Measurements of gas phase soluble bromide in the boundary layer and in firn air, and Br − in aerosol and snow, were made at Summit, Greenland (72.5 • N, 38.4 • W, 3200 m a.s.l.) as part of a larger investigation into the influence of Br chemistry on HO x cycling. The soluble bromide measurements confirm that photochemical activation of Br − in the snow causes release of active Br to the overlying air despite trace concentrations of Br − in the snow (means 15 and 8 nmol Br − kg −1 of snow in 2007 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 42 publications
7
59
1
Order By: Relevance
“…Our analysis is consistent with the results of Dibb et al (2010), who also concluded that bromide in the snow is photochemically activated and released into the boundary layer. The levels of BrO from this mechanism are modulated by the actinic flux and the diurnal evolution of the boundary layer.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our analysis is consistent with the results of Dibb et al (2010), who also concluded that bromide in the snow is photochemically activated and released into the boundary layer. The levels of BrO from this mechanism are modulated by the actinic flux and the diurnal evolution of the boundary layer.…”
Section: Discussionsupporting
confidence: 82%
“…Summit is located on top of the Greenland ice sheet at 3200 m altitude and, with a distance of at least 400 km from the nearest ocean, removed from large halogen sources. Small amounts of chloride and bromide are found in surface snow at Summit (see Dibb et al, 2010), but it is to date unclear if reactive gaseous halogens are present at sufficiently high levels to have an influence on atmospheric chemistry.…”
mentioning
confidence: 99%
“…3. Overall the levels of BrO were lower and less diurnally consistent in 2008 compared to 2007, even when comparing the same June overlap period Liao et al, 2011;Dibb et al, 2010). Total mercury in surface snow was slightly less in 2008 than in 2007 during the overlap period, and GEM showed significantly less variation in 2008.…”
Section: Resultsmentioning
confidence: 95%
“…These stable conditions change to neutral or slightly unstable conditions resulting in enhanced mixing depths of ∼70-250 m during an ∼8 h "daytime" period centered around local solar noon (Helmig et al, 2002). Chemical species thought to be emitted from the snowpack, such as NO and often BrO, showed diurnal profiles with minima at solar noon due to a larger mixing volume (Thomas et al, 2011a;Dibb et al, 2010). While a portion of the RGM and FPM diurnal dips, during 7-13 June 2008 period (Fig.…”
Section: Results From Selected Periodsmentioning
confidence: 99%
“…Brooks et al (2011) concluded to the existence of bromine and mercury chemistry. It was suggested that snowpack photochemistry could be a possible source of BrO to the atmosphere (Dibb et al, 2010;Stutz et al, 2011). However the sources of bromide remained unclear and could be the falling snow and the transport of some bromine species from the free troposphere or marine regions.…”
Section: Examining Oxidation Pathways With Halogensmentioning
confidence: 99%